Reversible color video watermarking scheme based on hybrid of integer-to-integer wavelet transform and Arnold transform - Fahad Layth Malallah; Awatif Ali Jafaar; Nidaa Hasan Abbas; Mustafa Ghanem Saeed (Institute of Advanced Engineering and Science, 2020)
Unauthorized redistribution and illegal copying of digital contents are serious issues which have affected numerous types of digital contents such as digital video. One of the methods, which have been suggested to support copyright protection, is to hide digital watermark within the digital video. This paper introduces a new video watermarking system which based on a combination of Arnold transform and integer wavelet transforms (IWT). IWT is employed to decompose the cover video frames whereby Arnold transform is used to scramble the watermark which is a grey scale image. Scrambling the watermark before the concealment makes the transmission more secure by disordering the information. The system performance was benchmarked against related video watermarking schemes, in which the evaluation processes consist of testing against several video operations and attacks. Consequently, the scheme has been demonstrated to be perfectly robust.